PELATIHAN MANAJEMEN KEUANGAN DAN INVESTASI UNTUK MENINGKATKAN LITERASI DAN SKILL KEUANGAN MAHASISWA - Maha Putri, Dhika; Narullia, Dwi; Habibatus Sholihah, Finna (Universitas Mataram, 2025)
Personal finance is a skill that must be mastered and applied for life. However, mastering personal finance skills is still a challenge for students. Many students are trapped in online loans (pinjol) due to their lack of ability to manage personal finances effectively. This condition shows a significant gap in the mastery of financial skills, which if left unchecked can trigger bigger financial problems in the future. Based on this, this service activity was carried out to provide education and training on personal finance while introducing various investment instruments. The main goal is to help students manage their finances wisely and encourage them to start investing, in order to build long-term financial stability and avoid dependence on loans. The training participants came from universities and state universities in Malang City with a total of 30 participants. The service was conducted offline at the Malang Creative Center Building on the 4th floor with a duration of 3 hours. The materials provided include basic personal finance, personal finance pyramid, basic money management, and various investment instruments. The survey results showed that the service participants gained an understanding of financial management. Participants were able to identify steps in managing their personal finances more structurally and wisely, and began planning investments as part of a long-term financial strategy.